Common gynecological morbidities among married women in a resettlement colony of East Delhi - Mathur, Mansi; Das, Ranjan; Vibha, . (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: A women is always celebrated for child birth but gynaecological issues a stigma is attached. The fear of being ostracised by the society for gynaecological problems is deep set. Gynaecological morbidity is defined as “structural and functional disorder of genital tract not related to pregnancy, delivery or perpuerium”. This paper aims to study the pattern of gynaecological morbidity among married women residing in a resettlement colony of East Delhi. Methods: A community based cross-sectional study was conducted during 2014-2015 in the field practise area of Lady Hardinge Medical College, New Delhi. A self-designed, pre-tested questionnaire was used to collect data. All married women of reproductive age (15-49 years) who were willing to participate were included in the study. Results: The mean age of study subjects was 34.6±8.5 years with a range of 18-49 years. All women in study had menarche within normal range (mean age =13.1±1.01 years, range: 11-16 years). Mean age at marriage was 20.6±2.4 years, range: 15-25 years. Nearly 40% of women had 3 children and most women above 40 years of age had three or more children. The mean parity was 2.04±0.5. Mean age at first delivery for study subjects was 22.1±3.9 years. In the present study 722 (59.5%) of the 1214 study subjects had one or more symptom related to common gynaecological morbidities. Among symptomatic 594 out of 277 (82%) had one symptom. The commonest symptom was ‘lower abdominal pain during menstrual period’ 419 (34.5%) followed by symptoms of premenstrual syndrome [(such as ‘bloating’ 328 (27%) and ‘irritability’ 269 (22.2%) and ‘breast tenderness’ 218 (18%)]. Other symptoms observed were ‘scanty blood loss’166 (13.7%), ‘shortened duration of blood flow’ 149 (12.2%) and ‘something coming out of vagina’140 (11.5%). Conclusions: Gynaecological morbidities in spite of their preponderance and adverse health outcomes, have not attracted the attention due to it for two reasons: i) women in most patriarchal dominated societies do not speak out of their health problems and needs, more so if that is not connected to the birth process, ii) Health care providers and institutions had been so overwhelmed with the birthing process, and now the expanded reproductive health issues that attending to gynaecological morbidities was considered to be “luxury” in as far as public health was considered.